Solid state bioconversion of oil palm empty fruit bunches for production of citric acid by wild strains of Aspergillus niger - Alam, Md. Zahangir; Bari, Md. Niamul; Muyibi, Suleyman Aremu; Jamal, Parveen; Al-Mamun, Abdullah (Taylor and Francis, 2010)
This study investigated the potential of Aspergillus niger strains for the production of citric acid from oil palm empty fruit bunches (EFB) through solid state bioconversion (SSB). Twenty six wild strains of Aspergillus niger isolated from lemon, orange, and sewage treatment plant sludge were evaluated. Factors considered in the study were citric acid production, sugar consumption, and protein content as growth indicator. Two strains of Aspergillus niger (IBO-103MNB) and (IBO-114MNB) were found to have good potential with citric acid production of 128.43 ± 6.3 and 140.50 ± 1 g kg-1 of dry EFB with bioconversion time of 4 and 8 d, respectively. The productivity of citric acid by these strains was found to be 32 and 17.5 g kg–1d–1, respectively.